THE USE OF OPIOIDS IN PAIN MANAGEMENT IN CANCER PALLIATIVE CARE: BENEFITS AND RISKS (REMUNOM, 2025)
Introduction: Opioids are substances with pharmacological properties similar to opiates, derived from opium, which is extracted from Papaver somniferum. These drugs have broad clinical applications, particularly in oncological palliative care, where pain management is one of the primary challenges. Objective: To discuss the implications of opioids in pain treatment for patients with advanced cancer, highlighting both their benefits and associated risks. Methodology: This study utilized an integrative literature review, formulating the question: "What is the impact of opioids on pain management in oncological palliative care?" Searches were conducted in the SCIELO, PUBMED, and LILACS databases using descriptors such as "opioids," "palliative care," and "pain management." Articles from 2014 to 2024 were included, in Portuguese, English, and Spanish, that addressed the use of opioids in palliative care. Results: The search yielded 2,557 articles, of which 103 were selected after reading the title and abstract, and 15 articles were included following full analysis. Key findings include reviews on opioid classification, studies on their effectiveness in pain control, and discussions on the risks of adverse effects, such as respiratory depression and tolerance. Discussion: Palliative care aims to improve the quality of life for patients and their families in the face of serious illness, focusing on pain relief. Opioids are effective for pain control but present side effects and may contribute to indirect euthanasia. Conclusion: Opioids are essential in palliative care, but their use requires careful management to avoid adverse effects, focusing on alleviating suffering with an ethical approach